Component Testing for VsImaging Library Using Pixel Comparison Technique - Muhammad Zulfahmi Toh, Abdullah; Abbas Saliimi, Lokman; Ku Saimah, Ku Ibrahim (2013)
Testing the image similarity between two images is a non-trivial task. Image is not a quantitative data input and output. Image contains several complex properties that can be evaluated. In the present paper, properties like height, length and pixel between the two image are compare to get the similarly of the component testing from the VSImaging library image output with the expected image from the library to validate the output image are match the criteria of the expected output image. Furthermore these paper will explain the automatic unit testing of the VSImaging component will be conducted.